An error anlysis on english descriptive text at the first grade of junior high school - Dian Shinta Sari; Istiqomah Istiqomah; Maliqul hafis (IKIP PGRI Pontianak, 2022)
Abstract This research consists of problems, objectives, methods, findings, and conclusions of Error Analysis in English Descriptive Text at the First Grade of Junior High School. This study aimed to determine the types of grammatical errors, the most dominant errors and to analyze the causes of grammatical errors made by students in writing descriptive text essays. This research was conducted on grade I students of SMP Assalam Pontianak in the academic year 2021/2022. the total population is 94 students from three classes. The sample was grade one C which consists of 35 students. This type of research uses descriptive analysis with a qualitative approach. Data collection techniques used were direct communication techniques and documentation. Data collection tools were interview guides and student worksheets. This study found that from 35 students who had made descriptive texts, there were 402 grammatical errors. The data collected were from 61 English essays written by 35 students. Data were analyzed based on student worksheets and interview transcripts to find the types of errors and dominant errors and the causes of errors. Based on data analysis, the results of this study showed that the errors of 35 students in producing English writing were (1) misformation 47%, (2) omission 40%, (3) Addition 10%, and (4) misordering 3%. Based on the results of the interview, it can be classified that translation was the main cause of grammatical errors.